Performance tests and comparison of microdosimetric measurements with four tissue-equivalent proportional counters in scanning proton therapy. (January 2017) - Farah, J.; De Saint-Hubert, M.; Mojżeszek, N.; Chiriotti, S.; Gryzinski, M.; Ploc, O.; Trompier, F.; Turek, K.; Vanhavere, F.; Olko, P.
Abstract: This paper compares the performance of four different Tissue-Equivalent proportional counters (TEPC) first in standard radiation fields, with gamma and neutron sources, then in the mixed and complex/intense neutron and photon stray radiation field of a scanning proton therapy facility. The paper focuses on the dead time correction and introduces a new spectra processing methodology to enable the comparison of the four TEPCs while accounting for their different gas filling and gain, lineal energy range of the spectrum and the analysis methodology. Measurements with 137 Cs and/or 60 Co gamma sources demonstrate variable low-LET threshold for each TEPC while data acquired with a 252 Cf neutron source show comparable response of the four TEPCs for high-LET particles. Meanwhile, in the scattered field of proton therapy, microdosimetric spectra measured at different positions and orientations around the patient show a majority of high-LET events at the smallest angle with respect to the beam axis while low-LET particles were mainly dominant at 90° from the beam axis. The introduced processing methodology led to good overlapping of microdosimetric spectra for the four systems. Highlights: Intercomparison of four commercial TEPCs in standard and complex radiation fields. Methodology to convert propane to propane-TE spectra and extrapolate low-LET events. TEPCs provide critical data to monitor proton therapy's stray radiation environment. HAWKs' proton edge position, set by the manufacturer, remains controversial. Calibration and processing of TEPCs involve several challenges and open questions.